Endangered flora of Gdańsk Pomerania – its distinctiveness and diversity - Wszałek-Rożek, Katarzyna; Lazarus, Magdalena; Afranowicz-Cieślak, Renata; Gołębiewska, Joanna; Kuczyńska, Anna; Jarosińska, Marta; Eichmann, Artur; Markowski, Ryszard (Biodiversity: Research and Conservation, 2018)
Gdańsk Pomerania is a region characterized by unique physiographic features and diverse flora. This region, as many other areas, is subject to numerous accelerating transformations. The occurrence of numerous species on their range edges and on isolated stands, e.g. mountain and xerothermic grassland species, was an important criterion in the development of a regional red list of vascular plants of Gdańsk Pomerania . On this list, 648 species of vascular plants, which constitute about 39% of the regional flora and 26% of all Polish flora, are considered to be endangered at various levels. In total, 47 species have been declared extinct in the aforementioned region (RE), 39 taxa are considered as critically endangered (CR) and 109 – as endangered (EN). Further 222 plant species are classified as vulnerable (moderately endangered) (VU), 124 have low risk categories (NT or LC) and there are 107 taxa of unknown threat, due to lack of sufficient information (DD). The aim of this work was to synthesize endangered components of Gdańsk Pomerania vascular plant flora for their better recognition and characterization. Among the species varying in threat degrees, the authors identified species protected by law and endangered in Poland as well as globally. In addition, the participation of species diagnostic of individual phytosociological units was verified. Also, the share of taxa representing various geographical elements was indicated.